2012
DOI: 10.5483/bmbrep.2012.45.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of Hanwoo (native Korean cattle) cloned from somatic cells of a single adult

Abstract: We investigated phenotypic differences in Hanwoo cattle cloned from somatic cells of a single adult. Ten genetically identical Hanwoo were generated by somatic cell nuclear transfer from a single adult. Weights at birth, growing pattern, horn and noseprint patterns were characterized to investigate phenotypic differences. The weights of clones at 6 and 12 months were slightly heavier than that of the donor. A horn pattern analysis revealed that seven clones had exactly the same horn pattern as the donor cow, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Selective sweep signatures may have contributed to the domestication process (3,4). Despite various Hanwoo (Korean native cattle) mapping and diversity studies (5,6), the identification of mutations affecting some quantitative phenotypes (7,8), and several expression studies (9-11), selective sweep signatures in these animals have not been identified. There have been several attempts to conduct such characterization at the population level of other cattle by detecting selective sweep signatures (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective sweep signatures may have contributed to the domestication process (3,4). Despite various Hanwoo (Korean native cattle) mapping and diversity studies (5,6), the identification of mutations affecting some quantitative phenotypes (7,8), and several expression studies (9-11), selective sweep signatures in these animals have not been identified. There have been several attempts to conduct such characterization at the population level of other cattle by detecting selective sweep signatures (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Large structural variations can be attributed to inversions and translocations, duplications, and deletions. Although existing at lower rates than SNPs, CNVs and INDELs comprise another important type of genomic variation (11) that can be used to better understand genome features.…”
Section: Introductionmentioning
confidence: 99%